DETERMINATION OF LOAD LIMITS ON DRIVE SHAFTS IN HOT ROLLING MILL - Darko Danev; Vase Jordanoska; Stevan Kjosevski (Mechanical Engineering – Scientific Journal, 2014)
Drive shaft breakages in rolling mills generate great material losses. Improving the strength characteristics of drive shafts should provide shafts to withstand the maximum loading during the rolling process. Breaking in the shaft critical section may occur when the value of the torque is greater than the value of the torsion moment which can cause plastic flow in the whole cross section. Theoretical calculations and experimental tests were done. The experiment showed that the maximum rolling torque of the upper shaft has a higher value than the torque limit at permanent torsion dynamic strength. The available safety reserves in the critical section were small, only 27%. To increase the strength characteristics, changing in the cross-section design and in material quality for shafts should be done.
Keywords: strength characteristics; drive shafts; torque